2000
DOI: 10.1074/jbc.m000753200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP-dependent Protein Kinase Signaling Pathway Inhibits RhoA-induced Ca2+ Sensitization of Contraction in Vascular Smooth Muscle

Abstract: The potent vasodilator action of cyclic GMP-dependent protein kinase (cGK) involves decreasing the Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
483
7
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(520 citation statements)
references
References 40 publications
22
483
7
5
Order By: Relevance
“…Here both cAMP-increasing agent and cGMP-increasing agent inhibited the association between PLD1 and Val14RhoA, although the possible physiological role of PKG in PLD signaling is unknown. This result indicates that RhoA phosphorylation by cAMP and cGMP may affect binding of RhoA to PLD1, since PKA and PKG phosphorylate serine188 on RhoA (Lang et al, 1996;Sauzeau et al, 2000;Sawada et al, 2001;Ellerbroek et al, 2003). Moreover, consistent with our findings, PKA-mediated phosphorylation decreased the binding of RhoA to another downstream effector molecule, Rho (Dong et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Here both cAMP-increasing agent and cGMP-increasing agent inhibited the association between PLD1 and Val14RhoA, although the possible physiological role of PKG in PLD signaling is unknown. This result indicates that RhoA phosphorylation by cAMP and cGMP may affect binding of RhoA to PLD1, since PKA and PKG phosphorylate serine188 on RhoA (Lang et al, 1996;Sauzeau et al, 2000;Sawada et al, 2001;Ellerbroek et al, 2003). Moreover, consistent with our findings, PKA-mediated phosphorylation decreased the binding of RhoA to another downstream effector molecule, Rho (Dong et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…To determine whether intracellular cAMP levels regulate the association between PLD1 and the active form of RhoA, RhoA was immunoprecipitated from cells treated with or without dbcAMP and the amount of co-precipitated PLD1 was measured. RhoA was reported to be phosphorylated at Ser188 by both PKA and PKG (Lang et al, 1996;Kwak and Uhlinger, 2000;Sauzeau et al, 2000;Sawada et al, 2001). dbcAMP or dbcGMP induced a marked increase in the phosphorylation of band co-localized with the immunodetected band of Val14-RhoA ( Figure 4B).…”
Section: Effect Of Phosphorylation On the Interaction Betw Een Pld1 Amentioning
confidence: 97%
“…On the other hand, several investigators have shown that NO blocks the migration of RhoA from the cytosol to the membrane, thereby inhibiting the RhoA/ROCK signaling pathway. 114,115 It is thought that there is an interaction between activated ROCK and endothelial dysfunction in human vessels. Indeed, we have confirmed that hypertension is associated with both endothelial dysfunction and increased ROCK activity, and that endothelial dysfunction and increased ROCK activity are simultaneously improved by an aldosterone blocker in patients with hypertension.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…(kinase-related protein of 17kDa), which has a similar amino acid sequence as myosin light chain kinase (MLCK) at COOH terminal with 156 amino acid, and promotes the dephosphorylation of myosin light chain 20 (MLC20), which is closed associated with the calcium sensitization 6 . The previous studies showed that PKG was involved in the calcium desensitization of vascular smooth muscle after hemorrhagic shock, which was possibly related to MLCK 3,7 .…”
Section: Protein Kinase G (Pkg) May Phosphorylate Telokinmentioning
confidence: 99%